The Effect of Apparatus Competence and the Effectiveness of the Regional Government Information System on the Quality of Financial Statements: A Case Study of the Jambi Provincial Government: Studi Kasus pada Pemerintah Provinsi Jambi - Naomi Sayuna. M; Ilham Wahyudi; Rita Friyani (International Journal of Economics, Business and Innovation Research, 2025)
The quantitative descriptive approach utilized in this research is derived from firsthand information collected fromfinancial authorities who are in charge of creating government financial reports via questionnaires. With the aid of SPSS software the information was examined employing multiple linear regression, t-test, and F-test. The outcomes demonstrate that: (1) The quality of financial reports is positively impacted by civil servant competency, yet this effect is not statistically significant because the statistical importance level is 0.080, which exceeds 0.05; (2) With a statistical importance level of 0.000, which falls below0.05, the efficacy of SIPD results in a favorable and statistically significant impact on financial reporting standards; and (3) Additionally, they had a affirmative and considerable combined impact on the Jambi Provincial Government's fiscalreporting standards when examined simultaneously, with an F-statistic of 51.580 and a statistical importance level of 0.000. These findings suggest that a key factor in raising financial reporting standards is the efficacy of information systems. However, increasing public servant capability is still essential to making the most of SIPD.